ضوابط ستر عورة الملسلمة : دراسة تطبيقية في الجامعة الإسلامية العالمية ماليزيا - Nurjannah Hasmad (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
Islam commands it's female believers to cover their aurah, the body parts that are obliged by Allah upon the Muslims to be covered, as which had been clearly stated in numerous Quranic verses and prophetic traditions. Nevertheless, there are not many studies discussing the topic of aurah covering parameters, instead, the existing literatures in this topic mainly explore the meaning of hijab to Muslim women. Attempting to fill the gap, this study aims to determine the correctness of understanding on aurah covering parameters among female students in International Islamic University Malaysia (IIUM) and their differences in understanding regarding the matter. This study also aims to identify the factors that shape female IIUM students understanding regarding aurah covering parameters, as well as to identify the difference in the correctness of their understanding between those who are affected by these factors and those who were not affected. Another objective of this study is to find out the coherence of IIUM dress code with Islamic aurah covering parameter and the adherence of IIUM female students towards this dress code. The researcher used the inductive method to study the discussion of scholars deriving the evidence regarding aurah covering and the analytical method in analysing their opinions. In addition, the researcher adopted the quantitative method through survey conducted using questionnaire. The questionnaire was distributed online among female students of IIUM using various social media platform. The researcher obtained usable answers from 136 students, and these answers were analysed using the Statistical Package for Social Sciences (SPSS) program. The result show that IIUM female students possess correct understanding on aurah covering parameter and did not show significant difference of understanding on the matter. The two factors that shape female IIUM students understanding regarding aurah covering parameters are the religious sources and family. The researcher found statistically significant difference in the correctness of understanding between those who are affected by these factors and those who were not affected. The results also show that the university dress code is in line with the aurah covering parameters in general, except in the clause prohibiting face covering in the university compound. Furthermore, the results show good adherence of IIUM female students to the dress code.